ANIMASI 3 DIMENSI SEBAGAI SARANA SOSIALISASI PENTINGNYA KECERDASAN EMOSIONAL DALAM KEHIDUPAN REMAJA - Ronald Tanga Ili Watun; Gde Lingga Ananta Kusuma Putra; Yasa, Gede Pasek Putra Adnyana (Institut Bisnis dan Teknologi Indonesia, 2019)
In general, every human being must face problems and trials of life. There are various kinds of problems that come in life, do not know when, where and how these problems come. In dealing with problems, humans have their own ways to overcome these problems. There are those who give up easily and some who can overcome them. In this case the role of emotional intelligence is very important. Especially at the age of adolescence sometimes difficult to control emotions in themselves, resulting in a sense of hopelessness. Therefore, it is necessary to design a media that can be used to socialize the importance of emotional intelligence in adolescent life. The results showed that the concept that was appropriately used to socialize the importance of emotional intelligence in adolescents' lives was the concept of